China's Christian colleges : cross-cultural connections, 1900-1950 - Bays, Daniel H.; Widmer, Ellen (Stanford, Calif. : Stanford University Press, 2009)
China's Christian Colleges explores the cross-cultural dynamics that existed on the campuses of the Protestant Christian colleges in China during the first half of the twentieth century. Focusing on two-way cultural influences rather than on missionary efforts or Christianization, these campuses, most of which were American-supported and had a distinctly American flavor, were laboratories or incubators of mutual cultural interaction that has been very rare in modern Chinese history. In this Sino-foreign cultural territory, the collaborative educational endeavor between Westerners and Chinese created a highly unusual degree of cultural hybridity in some Americans and Chinese. The thirteen essays of the book provide concrete examples of why even today, more than a half-century after the colleges were taken over by the state, long-lasting cultural results of life in the colleges remain.
pt. 1. The call : the Student Volunteer Movement for Foreign Missions. The SVM and transformation of the Protestant mission to China / Terrill E. Lautz -- pt. 2. Foundations of the college enterprise. American geometries and the architecture of Christian campuses in China / Jeffrey W. Cody -- Science, religion, and the classics in Christian higher education to 1920 / Ryan Dunch -- The seven sisters and China, 1900-1950 / Ellen Widmer -- pt. 3. Curriculum and careers. Liberal arts education in English and campus culture at St. John's University / Edward Yihua Xu -- The professionalization of Chinese domesticity : Ava B. Milam and home economics at Yenching University / Helen Schneider -- Anglo-American law at Soochow University / Alison W. Conner -- From Lingnan to Pomona : Charles K. Edmunds and his Chinese American career / Dong Wang -- pt. 4. Wider ramifications. National salvation : teaching civic duty in China's Christian colleges / Susan Rigdon -- Same bed, different dreams : the American postwar plan for China's Christian colleges, 1943-1946 / Jiafeng Liu -- China's Christian colleges and the founding of the Harvard-Yenching Institute / Paul Daniel Waite and Peichi Tung Waite -- pt. 5. Beyond China. A Japanese American enterprise : Umeko Tsuda's Bryn Mawr network and the founding of Tsuda College / Yuko Takahashi -- Cyrus Hamlin in Turkey / Ted Widmer.
Includes bibliographical references (pages 371-393) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Christian universities and colleges -- China -- History -- 20th century -- Congresses; Education, Higher -- China -- History -- 20th century -- Congresses; China -- Relations -- United States -- Congresses; United States -- Relations -- China -- Congresses; Electronic books; Universités confessionnelles -- Chine -- Histoire -- 20e siècle -- Congrès.; Enseignement supérieur -- Chine -- Histoire -- 20e siècle -- Congrès.; Livres numériques.; e-books.; EDUCATION -- Higher; Electronic books; Christian universities and colleges; Education, Higher; International relations; China; United States; Christentum; College; China; 1900-1999; Geschichte 1900-1950.; proceedings (reports); Conference papers and proceedings; History; Electronic books; Conference papers and proceedings; Actes de congrès.